First Report of the Hyperaccumulating Potential of Cadmium and Lead by Cleome rutidosperma DC. With a Brief Insight Into the Chemical Vocabulary of its Roots - Bhattacharya, Ekta; Mandal Biswas, Suparna (Frontiers in Environmental Science, 2022)
Phytoremediation is gaining interest in recent years as a simple and effective strategy for heavy metal decontamination. The most straightforward strategy for successful heavy metal clean-up is searching for efficient hyperaccumulator species that grow naturally in contaminated sites. The present study, therefore, is the first detailed account of hyperaccumulator potentialities of a neglected and underutilized (NUS) species Cleome rutidosperma DC. Hydroponic screening experiment against Cadmium and Lead revealed that even at 10 mg/kg concentration, it could accumulate 42.49 mg/kg of Cd and 27.79 mg/kg of Pb in shoots while 134.71 mg/kg Cd and 491.35 mg/kg of Pb in its roots and these values were significantly higher than the control plants. This plant could efficiently accumulate as high as 639.07 mg/kg of Cd, 8726.03 mg/kg of Pb in its roots while 752.83 mg/kg Cd and 3732.64 mg/kg Pb in its shoots as evident from the pot experiments. In case of Cd, there was no significant effect of toxicity on the phytophisiological parameters. But increasing concentrations of Pb did have toxic effects on total chlorophyll content. This plant showed to have a BCF >1 in most of the tested concentrations. At the highest treatment concentration, however, both the BCF and TF was found to be greater than 1. This indicated that C. rutidosperma can accumulate as well as translocate the heavy metals to its aerial parts when the metal concentration is extremely high proving itself to be an efficient hyperaccumulator. In order to decode the chemical signals this plant may emit through the roots to cope the stress, root exudates were collected, purified and analysed through GCMS. This revealed the presence of five major compounds namely palmitic acid, linoleic acid, Oleic acid, campesterol and stigmasterol which mainly are metabolic markers for detoxification mechanisms triggered by various stresses. Therefore, based on this study, C. rutidosperma can be termed as a potent hyperaccumulator and can further be exploited for remediation of other class of environmental pollutants.